PENENTUAN NILAI SUN PROTECTION FACTOR (SPF) SINAR MATAHARI DENGAN MENGGUNAKAN KAIN KATUN, POLIESTER DAN RAYON DI PANTAI KUTA - Winiayu Veramika, Ni Putu; Sutapa, I Gusti Ngurah; Ratini, Ni Nyoman (BULETIN FISIKA; Vol 17 No 1 (2016): BULETIN FISIKA, 2016)
This research has been determined the value of a sun protection factor (SPF) of sunlight by using cotton, rayon, and polyester conducted at ten observation points along Kuta Beach, Bali. This research started by determination the intensity of the sunlight without fabric protector and the intensity of sunlight with a fabric protector such as cotton, rayon, and polyester with color blue, green, red, and yellow. Luxmeter is used to measure the intensity of sunlight in units of lux. The intensity was taken at the sunny weather in the range 10-11 o’clock to 16-17 o’clock. SPF value can be calculated by comparing the intensity of the sunlight without fabric protector (lux) with the intensity of sunlight with a fabric protector (lux). The intensity of sunlight in the range of 10-11 o’clock to 16-17 o’clock is approximately 59.760 lux to 138.660 lux. ANOVA analysis showed the intensity of sunlight at each point of observation did not differ significantly ( . SPF value at each point varies and SPF values obtained for the maximum is the blue cotton fabric with SPF value is 30 and the minimum value is the yellow  polyester fabric with SPF value is 3.